2017
DOI: 10.29252/jhs.5.3.35
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Effective Factors on Gastric Cancer Using Frailty Model in South-East and North of Iran

Abstract: Background and Purpose: Gastric cancer is the third leading cause of mortality in Iran after cardiovascular diseases and accidents. The aim of the present study was to assess survival and it's affecting factors in gastric cancer patients through using Cox and parametric models along with frailty. Materials and Methods: In this study, the medical records of gastric cancer patients treated from 2008 to late 2010 were collected in Afzalipour and Bahonar Hospitals in Kerman and Imam Khomeini Hospital in Sari. 383 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…32 Conversely, the results of the study in Iran using the Frailty model showed no significant relationship between opium use and survival rate. 33 The limitations of the present study were incomplete information and a low sample size. On the other hand, the strength of this study is the results obtained using MSMs.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…32 Conversely, the results of the study in Iran using the Frailty model showed no significant relationship between opium use and survival rate. 33 The limitations of the present study were incomplete information and a low sample size. On the other hand, the strength of this study is the results obtained using MSMs.…”
Section: Discussionmentioning
confidence: 76%
“…32 Conversely, the results of the study in Iran using the Frailty model showed no significant relationship between opium use and survival rate. 33 …”
Section: Discussionmentioning
confidence: 99%
“…In survival analysis, this random effect is known as frailty. 1315 In studies of frailty models, the continuous frailty random variable is usually used. One of the most common and widely used is gamma distribution continuous distributions.…”
Section: Introductionmentioning
confidence: 99%